CUSTOMTOOLS as general integration platform for SOLIDWORKS - ERP data exchange - Erkinheimo, Simo (My University, 2021)
This thesis introduces the extreme complexity behind CAD – ERP integrations in real world scenarios as a reasoning why a general-purpose integration for all system variations simply does not exist. Delivered integrations are mostly fully customized projects, solving the same issues repeatedly with varying success and promise of usability. To attempt at least some level of generalization, the CAD system is chosen to be SOLIDWORKS, and CUSTOMTOOLS for SOLIDWORKS is chosen to provide partial solution by itself as well as an integration platform for any target ERP system. Subject matter expertise is first heavily relied on determining the most common requirements of SOLIDWORKS – ERP integrations and design science methodology is used to generalize a solution. CUSTOMTOOLS Profile is configured to meet some of the requirements and CUSTOMTOOLS API is thoroughly examined for meeting the rest, eventually resulting in generalized solution in the form of data model configuration rules and integration base implementation, embedded in the CUSTOMTOOLS core product. The true complexity of the common requirements can be easily seen in the generalized solution architecture, and benefits of the provided solution are recognized by consulted SOLIDWORKS - EPR integration project experts. The provided solution will be taken in use for future integration projects.
Keywords: ERP, CAD, integrations, SOLIDWORKS, CUSTOMTOOLS